Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's solve the quadratic equation [tex]\[x^2 + 11x + \frac{121}{4} = \frac{125}{4}.\][/tex]
1. Subtract [tex]\(\frac{125}{4}\)[/tex] from both sides to form a standard quadratic equation:
[tex]\[ x^2 + 11x + \frac{121}{4} - \frac{125}{4} = 0 \][/tex]
2. Combine like terms on the left side:
[tex]\[ x^2 + 11x + \frac{121 - 125}{4} = 0 \][/tex]
[tex]\[ x^2 + 11x - 1 = 0 \][/tex]
3. Solve the quadratic equation [tex]\(x^2 + 11x - 1 = 0\)[/tex].
We use the quadratic formula [tex]\(x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = 11\)[/tex], and [tex]\(c = -1\)[/tex].
First, calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = 11^2 - 4(1)(-1) = 121 + 4 = 125 \][/tex]
Next, find the solutions using the quadratic formula:
[tex]\[ x = \frac{{-11 \pm \sqrt{125}}}{2} \][/tex]
Notice that [tex]\(\sqrt{125} = 5\sqrt{5}\)[/tex]. So the solutions can be rewritten as:
[tex]\[ x = \frac{{-11 \pm 5\sqrt{5}}}{2} \][/tex]
Thus, there are two solutions:
[tex]\[ x_1 = \frac{{-11 + 5\sqrt{5}}}{2} \quad \text{and} \quad x_2 = \frac{{-11 - 5\sqrt{5}}}{2} \][/tex]
4. Evaluate the given options:
- [tex]\(x = -11 \pm \frac{25}{2}\)[/tex]:
- [tex]\(-11 + \frac{25}{2} = -11 + 12.5 = 1.5\)[/tex]
- [tex]\(-11 - \frac{25}{2} = -11 - 12.5 = -23.5\)[/tex]
- [tex]\(x = -\frac{11}{2} \pm \frac{25}{2}\)[/tex]:
- This would correspond to:
- [tex]\(\frac{-11 + 25}{2}\)[/tex]
- [tex]\(\frac{-11 - 25}{2}\)[/tex]
Which would be incorrect, as the discriminant terms differ.
- [tex]\(x = -11 \pm \frac{5\sqrt{5}}{2}\)[/tex]:
- [tex]\(-11 + \frac{5\sqrt{5}}{2}\)[/tex]
- [tex]\(-11 - \frac{5\sqrt{5}}{2}\)[/tex]
- [tex]\(x = -\frac{11}{2} \pm \frac{5\sqrt{5}}{2}\)[/tex]:
- These represent:
- [tex]\(\frac{-11 + 5\sqrt{5}}{2}\)[/tex]
- [tex]\(\frac{-11 - 5\sqrt{5}}{2}\)[/tex]
But we need our solutions [tex]\(x_1 = \frac{-11 + 5\sqrt{5}}{2}\)[/tex] and [tex]\(x_2 = \frac{-11 - 5\sqrt{5}}{2}\)[/tex].
Final Correct Options:
[tex]\[ x = -11 \pm \frac{5\sqrt{5}}{2} \quad \text{and} \quad x = -\frac{11}{2} \pm \frac{5\sqrt{5}}{2} \][/tex]
---
Our numerical results are approximately [tex]\(x \approx -11.0901699437495\)[/tex] and [tex]\(x \approx 0.0901699437494742\)[/tex] after evaluating these expressions directly. So [tex]\(x\)[/tex] values must align with [tex]\(-\frac{11 + 5\sqrt{5}}{2}\)[/tex] approximately [tex]\(-5.5+\pm 5\sqrt{5}=1.58358\pm-23.5\)[/tex], matching correct bracketed results:
[tex]\[ (-5.5+\pm 5)/\sqrt(5)+4,5*\sqrt(4,5-(-1.4/2)=(-\approx \1.5,\approx -23.5)\][/tex]+=[-, .
1. Subtract [tex]\(\frac{125}{4}\)[/tex] from both sides to form a standard quadratic equation:
[tex]\[ x^2 + 11x + \frac{121}{4} - \frac{125}{4} = 0 \][/tex]
2. Combine like terms on the left side:
[tex]\[ x^2 + 11x + \frac{121 - 125}{4} = 0 \][/tex]
[tex]\[ x^2 + 11x - 1 = 0 \][/tex]
3. Solve the quadratic equation [tex]\(x^2 + 11x - 1 = 0\)[/tex].
We use the quadratic formula [tex]\(x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = 11\)[/tex], and [tex]\(c = -1\)[/tex].
First, calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = 11^2 - 4(1)(-1) = 121 + 4 = 125 \][/tex]
Next, find the solutions using the quadratic formula:
[tex]\[ x = \frac{{-11 \pm \sqrt{125}}}{2} \][/tex]
Notice that [tex]\(\sqrt{125} = 5\sqrt{5}\)[/tex]. So the solutions can be rewritten as:
[tex]\[ x = \frac{{-11 \pm 5\sqrt{5}}}{2} \][/tex]
Thus, there are two solutions:
[tex]\[ x_1 = \frac{{-11 + 5\sqrt{5}}}{2} \quad \text{and} \quad x_2 = \frac{{-11 - 5\sqrt{5}}}{2} \][/tex]
4. Evaluate the given options:
- [tex]\(x = -11 \pm \frac{25}{2}\)[/tex]:
- [tex]\(-11 + \frac{25}{2} = -11 + 12.5 = 1.5\)[/tex]
- [tex]\(-11 - \frac{25}{2} = -11 - 12.5 = -23.5\)[/tex]
- [tex]\(x = -\frac{11}{2} \pm \frac{25}{2}\)[/tex]:
- This would correspond to:
- [tex]\(\frac{-11 + 25}{2}\)[/tex]
- [tex]\(\frac{-11 - 25}{2}\)[/tex]
Which would be incorrect, as the discriminant terms differ.
- [tex]\(x = -11 \pm \frac{5\sqrt{5}}{2}\)[/tex]:
- [tex]\(-11 + \frac{5\sqrt{5}}{2}\)[/tex]
- [tex]\(-11 - \frac{5\sqrt{5}}{2}\)[/tex]
- [tex]\(x = -\frac{11}{2} \pm \frac{5\sqrt{5}}{2}\)[/tex]:
- These represent:
- [tex]\(\frac{-11 + 5\sqrt{5}}{2}\)[/tex]
- [tex]\(\frac{-11 - 5\sqrt{5}}{2}\)[/tex]
But we need our solutions [tex]\(x_1 = \frac{-11 + 5\sqrt{5}}{2}\)[/tex] and [tex]\(x_2 = \frac{-11 - 5\sqrt{5}}{2}\)[/tex].
Final Correct Options:
[tex]\[ x = -11 \pm \frac{5\sqrt{5}}{2} \quad \text{and} \quad x = -\frac{11}{2} \pm \frac{5\sqrt{5}}{2} \][/tex]
---
Our numerical results are approximately [tex]\(x \approx -11.0901699437495\)[/tex] and [tex]\(x \approx 0.0901699437494742\)[/tex] after evaluating these expressions directly. So [tex]\(x\)[/tex] values must align with [tex]\(-\frac{11 + 5\sqrt{5}}{2}\)[/tex] approximately [tex]\(-5.5+\pm 5\sqrt{5}=1.58358\pm-23.5\)[/tex], matching correct bracketed results:
[tex]\[ (-5.5+\pm 5)/\sqrt(5)+4,5*\sqrt(4,5-(-1.4/2)=(-\approx \1.5,\approx -23.5)\][/tex]+=[-, .
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.